INTRAVITREAL ANTI-VASCULAR ENDOTHELIAL GROWTH FACTOR INJECTIONS for EXUDATIVE RETINAL ARTERIAL MACROANEURYSMS - Ahmad M. Mansour (2020)
© 2019 Ophthalmic Communications Society, Inc. Purpose:There is no established therapy for exudative-hemorrhagic complications in primary retinal arteriolar macroaneurysm (RAM).Methods:Retrospective multicenter interventional study of anti-vascular endothelial growth factor in symptomatic RAMs. Central macular thickness in m and best-corrected visual acuity in logMar were correlated with the RAM size and distance to the macula. Statistical analyses were performed using paired comparisons and Pearson correlation.Results:Thirty-two eyes (32 patients) were treated with a mean of 2.7 injections over a mean follow-up of 16.6 months. Initial best-corrected visual acuity correlated with the RAM size and distance to the macula (P = 0.02). Central macular thickness decreased by 131,180, and 211 m at 1, 2, and 3 months after the first injection (P < 0.001). Best-corrected visual acuity improved by 0.47 and 0.38 Early Treatment Diabetic Retinopathy Study lines at 2 and 3 months (P = 0.005). Anti-vascular endothelial growth factor response correlated with the RAM size (P = 0.04) and the distance to the macula (P = 0.009).Conclusion:Symptomatic RAMs can be treated successfully with anti-vascular endothelial growth factor injections, leading to a decrease in macular edema.